2020
DOI: 10.1101/2020.04.08.026906
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unravelling the effect of a potentiating anti-Factor H antibody on atypical hemolytic uremic syndrome associated factor H variants

Abstract: The complement system plays an important role in our innate immune system. Complement activation results in clearance of pathogens, immune complex and apoptotic cells. The host is protected from complement-mediated damage by several complement regulators. Factor H (FH) is the most important fluid-phase regulator of the alternative pathway of the complement system. Heterozygous mutations in FH are associated with complement-related diseases such as atypical hemolytic uremic syndrome (aHUS) and age-related macul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…This antibody can restore FH activity in aHUS patient sera (217). In addition, we recently showed that this potentiating antibody not only potentiates wild type FH, but also four common aHUS mutated FHs in vitro (218).…”
Section: Potentiating and Inhibiting Complement Regulation Using Antibodiesmentioning
confidence: 82%
See 1 more Smart Citation
“…This antibody can restore FH activity in aHUS patient sera (217). In addition, we recently showed that this potentiating antibody not only potentiates wild type FH, but also four common aHUS mutated FHs in vitro (218).…”
Section: Potentiating and Inhibiting Complement Regulation Using Antibodiesmentioning
confidence: 82%
“…As has been described above, there is a clear need for this in specific groups of PNH patients, that suffer from extravascular hemolysis under eculizumab treatment. Potentially, treatments based on complement regulatory proteins that target C3, could be a solution there, as for example FH-CR2, miniFH and anti-FH07 (197,218). Next, the successful in vivo tests of FH-IgG chimeric proteins in bacterial infections, indicate that there might lie success in similar approaches using C4BP, C1-INH or Vn, which all are used by bacteria in complement evasion mechanisms (19).…”
Section: Discussionmentioning
confidence: 99%
“… Omeros Factor H Anti-FH.07 Potentiating monoclonal antibody n.s. aHUS Preclinical Sanquin [ 129 , 130 ] AMY201 (Mini FH) Recombinant protein n.s. Age-related macular degeneration; PNH Preclinical Amyndas [ 131 , 132 ] FH, FHmoss Recombinant n.s.…”
Section: Complement Inhibition Nowadays and In The Futurementioning
confidence: 99%
“…By elaborating special detector geometries, we can image local electromagnetic fields inside materials through differential phase contrast (DPC) imaging techniques [1,2]. We have been continuously developing very fast area detectors that are capable of atomic-resolution STEM imaging.…”
mentioning
confidence: 99%